N06 The Introduction of Nurse Led Preconception and Pregnancy Education Clinics for patients with Inflammatory Bowel Disease. (30th January 2023) - Gleeson, S; Buckley, P M; McCarthy, D J; Moran, D C; O'Sullivan, C; O'Sullivan, G; O'Grady, D J; Sugrue, K
Abstract: Background: The Inflammatory Bowel Disease Centre in the Mercy University Hospital ( MUH) has a patient population of approximately 4000 patients with IBD, of these roughly half are women and many are diagnosed during their reproductive years. Caring for this patient cohort can be a challenge due to patient lack of knowledge surrounding IBD and pregnancy misinformation that can occur. The aim of this project was to identify the unmet education needs of patients in relation to pregnancy and IBD. Subsequent aims were to improve patient care through the establishment of IBD preconception and pregnancy education clinics Methods: An audit was carried out at the IBD infusion suite and Nurse led clinics over a 20-week period between April- August 2021. 448 patients between the ages of 18-45 were identified during this timeframe and asked to complete and IBD and pregnancy questionnaire. The questions to assess education needs were Q1) Are you planning pregnancy in the next 2years? Q2 Has your diagnosis of IBD affected your family planning in any way? Q3) Do you feel well informed/prepared from an IBD perspective to start/continue your family? Q4) Do you have any questions or concerns regarding IBD and pregnancy e.g. Disease flare up impact on pregnancy, mediation queries/concerns, impact of pregnancy disease process Q5) What do you feel the percentage risk of your baby developing IBD would be ( 0-10%, 10-20%, 20-40% or >40%) Q6 Would you be interested in attending a pregnancy education clinic led by and Advanced Nurse Practitioner? Results: 55% of respondents were women. 89% of respondents felt they needed more education on IBD and pregnancy. 70% of respondents were concerned about the impact of an IBD flare up on fetal health with 19% remaining voluntarily childless. 95% of patients had questions/concerns about the effects of biologic drugs on pregnancy outcomes. 90% of patients said they would attend IBD ANP led preconception and pregnancy education clinics. 84% of patients overestimated the percentage risk of their offspring developing IBD, with 59% estimating the risk to be greater than 20% Conclusion: This audit identified the need for preconception and pregnancy education clinics for patients with IBD to improve patient education, care and outcomes. ANP led preconception and pregnancy education clinics have been established since October 2021 & are ongoing. Currently between 8-12 patients attend exclusively for preconception counselling per month. Referrals are received from Consultants within the IBD Centre MUH